IONIZING RADIATION IN AGRICULTURE: PHYSICAL, BIOLOGICAL AND ONTOLOGICAL APPROACHES - Alves, Luis Felipe Medeiro; Arthur, Valter (Seven Editora, 2025)
Ionizing radiation has been present in agricultural and biological sciences for more than seven decades. Beyond its classical role in mutation breeding and food preservation, radiation has gained renewed attention as a tool for physiological stimulation at sublethal doses (a phenomenon known as radiohormesis). This chapter presents an integrative overview of the use of ionizing radiation in agriculture, addressing the physical principles, biological effects, and agronomic applications from a multidisciplinary perspective. Emphasis is placed on low-dose physiological responses, mechanisms of stimulation, and recent advances in digital knowledge systems that structure and disseminate information on radiobiological processes. The discussion aims to bridge traditional nuclear agronomy with modern approaches in ontology engineering and artificial intelligence for decision support. DOI: https://doi.org/10.56238/sevened2025.039-003